Impact of a cognitive stimulation program on the reading comprehension of children in primary education - Reina-Reina, Claudia; Conesa, Pedro J.; Duñabeitia, Jon Andoni (Frontiers in Psychology, 2023)
At present, numerous studies can be found in which influences and relationships between the principal executive functions, reading comprehension, and academic performance associated with reading are reported. However, there is still a lack of convergence regarding the impact of computerized cognitive training on children's executive development and its transfer in academic reading performance and comprehension of written texts. This study analyzes the effect of implementing a cognitive stimulation program on the performance of reading comprehension and academic performance in the subject of Spanish Language and Literature. To this end, a total sample of 196 children from 23 educational centers received the cognitive intervention for eight weeks, with three weekly sessions of between 15-20 minutes each occurring on non-consecutive days. Pre-test and post-test measurements were collected and analyzed. The results demonstrate a significant increase in the reading comprehension scores. In addition, a significant impact of the training on the participants’ academic performance in the subject Spanish Language and Literature was found. These results highlight the usefulness of computerized cognitive stimulation programs for reading comprehension enhancement.